A Theory of Economic Disintegration - Eckhard Janeba; Karl Schulz (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We develop a theory of economic disintegration with both endogenously formed tax and trade policies. We show very generally that, contrary to conventional wisdom, a country's disintegration from an integrated area leads to a deeper integration inside the area. Similarly, the departure of a country from a customs union lowers tariffs world-wide. Moreover, we introduce international firm mobility and non-cooperative business tax policies into the multi-country, multi-sector general equilibrium trade model of Melitz and Ottaviano (2008). We address the model-inherent dimensions of economic disintegration, such as tariffs, non-tariff barriers, the harmonization of production standards and regulations, business frictions, as well as household migration and analyze their effects on the domestic tax policies of asymmetric countries.
Keywords: F13; F15; F22; F53; H25; H73; 330; trade policy; tax/subsidy competition; oligopolistic markets; economic integration